Apples to apples or apples to oranges? International variation in reporting of process and outcome of care for out-of-hospital cardiac arrest - Nishiyama, C.; Brown, S.; May, S.; Iwami, T.; Koster, R.; Beesems, S.; Kuisma, M.; Salo, A.; Jacobs, Ian; Finn, Judith; Sterz, F.; Nurnberger, A.; et al. (Elsevier, 2014)
Objectives: Survival after out-of-hospital cardiac arrest (OHCA) varies between communities, due in part to variation in the methods of measurement. The Utstein template was disseminated to standardize comparisons of risk factors, quality of care, and outcomes in patients with OHCA. We sought to assess whether OHCA registries are able to collate common data using the Utstein template. A subsequent study will assess whether the Utstein factors explain differences in survival between emergency medical services (EMS) systems. Study design: Retrospective study. Setting: This retrospective analysis of prospective cohorts included adults treated for OHCA, regardless of the etiology of arrest. Data describing the baseline characteristics of patients, and the process and outcome of their care were grouped by EMS system, de-identified, and then collated. Included were core Utstein variables and timed event data from each participating registry. This study was classified as exempt from human subjects’ research by a research ethics committee. Measurements and main results: Thirteen registries with 265 first-responding EMS agencies in 13 countries contributed data describing 125,840 cases of OHCA. Variation in inclusion criteria, definition, coding, and process of care variables were observed. Contributing registries collected 61.9% of recommended core variables and 42.9% of timed event variables. Among core variables, the proportion of missingness was mean 1.9 ± 2.2%. The proportion of unknown was mean 4.8 ± 6.4%. Among time variables, missingness was mean 9.0 ± 6.3%. Conclusions: International differences in measurement of care after OHCA persist. Greater consistency would facilitate improved resuscitation care and comparison within and between communities.